Core-shell type fluororesin particles having improved bonding properties
By using perfluorinated resin cores of perfluorinated resins and acryloyl-based polymers in core-shell particles, combined with specific emulsifiers and polymerization methods, the problem of insufficient bonding strength of existing core-shell particles is solved, and excellent bonding characteristics and properties of electrode active materials are achieved.
Patent Information
- Application Number
- CN202380065210.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-07
- Filing Date
- 2023-04-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-04-21
AI Technical Summary
When used as the binder for electrode active materials, the existing core-shell particles have insufficient bond strength and the shell layer does not completely surround the core, affecting performance.
The core-shell particles of the perfluorinated resin core containing a perfluorinated resin core and the resin shell layer of an acryloyl-based polymer are polymerized by using specific emulsifiers and polymerization methods to form a uniform particle size and shell layer.
Excellent bonding characteristics with electrode active materials are achieved, providing excellent physical bonding, electrical and surface characteristics even in the case of using a small amount of perfluorinated resin core and core-shell particles.
Smart Images

Figure CN119855848A_ABST
Abstract
Description
Technical Field
[0001] The following disclosure relates to core-shell particles (or core-shell particulate binders) having a perfluorinated resin core comprising a perfluoropolymer and a resin shell layer comprising an acryl-based polymer, a composition comprising the core-shell particle, or an electrode made from the composition.
[0002] When the core-shell particles (or core-shell particulate binder) according to an exemplary embodiment of the present invention are used as a binder for electrode active materials, even when a small amount of perfluorinated resin core is used and a low content of core-shell particles is used, the binder that imparts bonding force or adhesive strength between electrode active materials can be sufficiently provided.
[0003] Furthermore, the core-shell particle according to an exemplary embodiment of the present disclosure may have a very uniform particle size distribution, have a very uniformly formed shell layer, and provide an excellent bonding effect. Background Art
[0004] Perfluorinated resins including polytetrafluoroethylene (PTFE) can be used as various adhesives, process improvers, fluidizers, etc. due to their electrical, thermal, and bonding properties.
[0005] For example, perfluorinated resins can be used together with other materials as coating materials for semiconductor manufacturing devices, coating materials on various substrates in electrical storage devices, adhesive materials, etc. In addition, in order to improve performance, research is being conducted to form a shell layer on the surface of particles with resins having different physical properties or by surface modification and improve the characteristics during use.
[0006] That is, in order to improve the surface characteristics while utilizing the properties of the perfluorinated resin as it is, a technology for producing core-shell particles in which the surface layer of the perfluorinated resin is a non-fluorinated resin shell layer has been developed.
[0007] Japanese Patent Publication No. JP 2019-112620 A discloses core-shell particles having a core comprising a perfluoropolymer and a shell comprising a non-fluorinated resin to provide core-shell particles with excellent dispersibility, but particles in which the shell layer does not completely surround the core may still be formed, and further, sufficient bonding strength is not shown, and therefore, the particles do not have sufficient performance to be used as a binder for electrode active materials. Summary of the invention
[0008] Technical issues
[0009] An object of the present disclosure is to provide a novel core-shell particle (or core-shell particulate binder) having a perfluorinated resin core having further improved bonding strength to an electrode active material or the like, and a resin shell layer comprising an acryl-based polymer, compared to conventional perfluorinated resins and core-shell particles or core-shell particulate binders comprising the same.
[0010] Technical Solution
[0011] In one general aspect, the core-shell particle comprises: a perfluorinated resin core comprising a perfluoropolymer and a resin shell layer comprising an acryl-based polymer, wherein the core-shell particle is prepared by using a C having one or more alkyl substituted C of the following chemical formula 1: 8 Or higher alkyl polyethylene glycol ether as an emulsifier, the acryl-based monomer is emulsified and polymerized to a perfluorinated resin core, and the acryl-based monomer comprises: (a) methyl methacrylate; (b) methacrylic acid or acrylic acid; and (c) C 2 To C 6 Alkyl (meth) acrylate:
[0012] [Chemical formula 1]
[0013] R-(-OC 2 H 4 -) n -OH
[0014] Wherein R is C substituted with one or more alkyl groups 8 or a higher alkyl group, and n is an integer of 5 to 15.
[0015] In an exemplary embodiment, Chemical Formula 1 may be an emulsifier of the following Chemical Formula 2:
[0016] [Chemical formula 2]
[0017]
[0018] In an exemplary embodiment, the perfluoropolymer may be polytetrafluoroethylene.
[0019] In an exemplary embodiment, the core-shell particle may include the perfluoropolymer and the acryl-based polymer in a weight ratio of 98:2 to 30:70.
[0020] In an exemplary embodiment, the core-shell particle may include the perfluoropolymer and the acryl-based polymer in a weight ratio of 80:20 to 40:60.
[0021] In an exemplary embodiment, the core-shell particle may include 20 wt % to 40 wt % of methyl methacrylate in the acryl-based monomer.
[0022] In an exemplary embodiment, the core-shell particle may include 30 to 50 wt % of methacrylic acid or acrylic acid in the acryl-based monomer.
[0023] In an exemplary embodiment, the core-shell particles may include 20 to 40 wt % of C in the acryl-based monomer. 2 To C 6 Alkyl (meth)acrylate.
[0024] In another general aspect, a composition comprises the core-shell particles and an electrode active material.
[0025] In another general aspect, an electrode made from the composition is provided.
[0026] In yet another general aspect, a battery comprises the core-shell particles as a binder.
[0027] Beneficial Effects
[0028] The core-shell particles according to an exemplary embodiment of the present disclosure show excellent bonding properties with other materials and can provide excellent physical bonding properties, electrical properties and surface properties even when using a small amount of a perfluorinated polymer such as polytetrafluoroethylene (PTFE). In addition, excellent bonding properties can be shown even when a small content of a core-shell particulate binder is used.
[0029] The core-shell particle according to an exemplary embodiment of the present disclosure may provide a core-shell particulate binder having a uniform particle size distribution and a very uniformly formed shell layer, and may also provide a new binder having excellent bonding strength to adhere particulate particles such as an electrode active material.
[0030] That is, the core-shell particles (or core-shell particulate binder) according to an exemplary embodiment of the present disclosure have excellent bonding properties with other materials such as metal or conductive particles, and have the effect of providing core-shell particles (or core-shell particulate binder) having excellent bonding properties even when a small amount of perfluorinated resin core and a small amount of core-shell particulate binder are used.
[0031] In addition, the core-shell particles according to an exemplary embodiment of the present disclosure are prepared by using a C having one or more alkyl groups substituted with the following Chemical Formula 1: 8 Or higher alkyl polyethylene glycol ether as an emulsifier, and make it by emulsion polymerization of acryl-based monomer, so as to form a uniform particle size and a uniform shell layer, so that the core of fluorine resin etc. is not exposed on the surface of the particle:
[0032] [Chemical formula 1]
[0033] R-(-OC 2 H 4 -) n -OH
[0034] Wherein R is C substituted with one or more alkyl groups 8 or a higher alkyl group, and n is an integer of 5 to 15.
[0035] The monomers forming the shell layer in the core-shell particles are acryl-based monomers, and the acryl-based monomers include (a) methyl methacrylate (MMA); (b) methacrylic acid (MAA) or acrylic acid (AA); and (c) C 2 To C 6 Alkyl (meth)acrylate.
[0036] Furthermore, since the core-shell particles and the core-shell particulate binder according to an exemplary embodiment of the present disclosure have excellent affinity with other materials such as electrode active materials, they can have the effect of fully showing the excellent binding characteristics of conventional fluororesins even when the content of the perfluoropolymer (PTFE) forming the perfluorinated resin core is very small, and furthermore, they can impart excellent binding characteristics to electrode active materials even in the case of a small content of the core-shell particulate binder.
[0037] In addition, by containing a shell layer prepared by polymerizing an acryl-based monomer, the core-shell particle according to an exemplary embodiment of the present disclosure has increased bonding strength with a metal current collector (e.g., Al foil) used as a current collector and materials (e.g., electrode active materials) even with a small content of fluororesin, thereby having the effect of further enhancing the physical properties of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a photograph of an electrode dough prepared according to Example 1.
[0039] Figure 2 is a particle shape analysis (FE-SEM) photograph of the electrode manufactured according to Example 1.
[0040] Figure 3 is a photograph of the electrode paste prepared according to Comparative Example 1.
[0041] Figure 4 This is a particle shape analysis (FE-SEM) photograph of the electrode manufactured according to Comparative Example 1. DETAILED DESCRIPTION
[0042] Hereinafter, a core-shell particle (or a core-shell particulate binder) having a perfluorinated resin core including a perfluoropolymer and a resin shell layer including an acryl-based polymer, a composition including the core-shell particle, or an electrode made from the composition will be described.
[0043] Unless otherwise defined, technical and scientific terms used in the specification have general meanings understood by those skilled in the art to which the present invention belongs, and descriptions of known functions and configurations that obscure the present invention will be omitted in the following description.
[0044] In addition, unless the context indicates otherwise, the singular forms used in the present disclosure may be intended to include the plural forms as well.
[0045] Furthermore, units not specifically mentioned used in the present disclosure are based on weight, and as an example, unless otherwise defined, units of % or ratios refer to weight % or weight ratio, and weight % refers to weight % of any one component in the total composition.
[0046] In addition, the numerical range used in the present disclosure includes all values within the range including the lower limit and the upper limit, the increments derived logically from the form and span of the defined range, all double-limited values, and all possible combinations of the upper and lower limits within the numerical range defined in different forms. Unless otherwise defined in the specification of the present invention, values that may exceed the numerical range due to experimental errors or rounding of values are also included in the defined numerical range.
[0047] The term "comprising" in the present disclosure is an open description having a meaning equivalent to terms such as "providing", "including", "having" or "characterized by", and does not exclude elements, materials or processes not further listed.
[0048] The term "(meth)acrylate" of the present disclosure may refer to both methacrylate and acrylate.
[0049] Hereinafter, a core-shell particle (or a core-shell particulate binder) having a perfluorinated resin core including a perfluoropolymer and a resin shell layer including an acryl-based polymer, a composition including the core-shell particle, or an electrode manufactured from the composition according to an exemplary embodiment of the present disclosure will be described.
[0050] The present disclosure relates to a core-shell particle (or a core-shell particle-like binder) having a perfluorinated resin core comprising a perfluoropolymer and a resin shell layer comprising an acryl-based polymer, wherein the core-shell particle (or core-shell particle-like binder) is prepared by using a C-substituted alkyl group having one or more alkyl groups of the following chemical formula 1: 8Or higher alkyl polyethylene glycol ether as an emulsifier, acryl-based monomer emulsion polymerization to the perfluorinated resin core to produce.
[0051] In an exemplary embodiment, the acryl-based monomer comprises (a) methyl methacrylate (MMA); (b) methacrylic acid (MAA) or acrylic acid (AA); and (c) C 2 To C 6 Alkyl (meth) acrylate:
[0052] [Chemical formula 1]
[0053] R-(-OC 2 H 4 -) n -OH
[0054] Wherein R is C substituted with one or more alkyl groups 8 or a higher alkyl group, and n is an integer of 5 to 15.
[0055] In an exemplary embodiment according to the present disclosure, Chemical Formula 1 may be an emulsifier of the following Chemical Formula 2, but is not limited thereto:
[0056] [Chemical formula 2]
[0057]
[0058] In an exemplary embodiment, the emulsifier may be polyethylene glycol trimethyl nonyl ether, in which the molecular weight of the ethylene glycol repeating unit showing hydrophilicity is 384 g / mol, but is not limited thereto.
[0059] In an exemplary embodiment, the core-shell particle (or core-shell particle-like binder) may provide an excellent particle shape, whereby a core-shell particle (or core-shell particle-like binder) having a shell layer uniformly surrounding the entire area of the core may be obtained.
[0060] In an exemplary embodiment, the monomer forming the perfluorinated resin core is not particularly limited as long as it is a perfluorinated unsaturated monomer, but for example, it can be at least one selected from the following: a polymer prepared from a monomer selected from tetrafluoroethylene (TFE), perfluoro(alkyl vinyl ether), hexafluoropropylene, etc., or a copolymer thereof, but is not limited thereto.
[0061] In an exemplary embodiment, examples of the perfluorinated polymer forming the perfluorinated resin core may be at least one selected from the group consisting of polytetrafluoroethylene (PTFE), tetrafluoroethylene (TFE) / perfluoro(alkyl vinyl ether) copolymer (PFA), and TFE / hexafluoropropylene copolymer (FEP), but are not limited thereto.
[0062] In an exemplary embodiment, the perfluoropolymer may be polytetrafluoroethylene, but is not limited thereto.
[0063] In an exemplary embodiment, the resin forming the resin shell layer may be a polyalkyl (meth)acrylate-based resin, but is not limited thereto.
[0064] In an exemplary embodiment, when the core-shell particles (or core-shell particulate binder) are produced by polymerization, they can be produced by conventionally known methods, such as a method by appropriately mixing a perfluorinated resin core and an additive (e.g., a polymerization initiator) and performing emulsion polymerization, solution polymerization, or suspension polymerization, but are not limited thereto.
[0065] In an exemplary embodiment, the core-shell particle (or core-shell particulate binder) may include a perfluoropolymer and an acryl-based polymer in the following weight ratios: 98:2 to 30:70, 95:5 to 30:70, 95:5 to 40:60, 95:5 to 50:50, 95:5 to 60:40, 95:5 to 70:30, 95:5 to 80:20, 90:10 to 30:70, 90:10 to 40:60. , 90:10 to 50:50, 90:10 to 60:40, 90:10 to 70:30, 90:10 to 80:20, 80:20 to 30:70, 80:20 to 40:60, 80:20 to 50:50, 80:20 to 60:40, 80:20 to 70:30, 70:30 to 30:70, 70:30 to 40:60, 70:30 to 50:50, or 70:30 to 60:40. Specifically, the core-shell particles may include the perfluoropolymer and the acryl-based polymer in a weight ratio of 98:2 to 30:70. Specifically, the core-shell particles may include the perfluoropolymer and the acryl-based polymer in a weight ratio of 80:20 to 40:60. The core-shell particles of the present disclosure have excellent affinity with active materials, and have an excellent effect of showing excellent binding characteristics with electrode active materials even when the ratio of the perfluorinated resin core (eg, perfluoropolymer (PTFE)) is low.
[0066] In an exemplary embodiment, the acryl-based monomer may include at least one selected from the group consisting of butyl methacrylate, 2-ethylhexyl methacrylate, hydroxyethyl methacrylate, glycidyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl methacrylate, methyl methacrylate, acrylic acid, methacrylic acid, ethyl acrylate, propyl acrylate, butyl acrylate, pentyl acrylate, and hexyl acrylate, but is not limited thereto. Specifically, the acryl-based monomer may include: (a) methyl methacrylate (MMA); (b) methacrylic acid (MAA) or acrylic acid (AA); and (c) C2 To C 6 Alkyl (meth) acrylate. More specifically, the acryl-based monomer may include: (a) methyl methacrylate (MMA); (b) methacrylic acid (MAA); and (c) butyl acrylate.
[0067] The core-shell particles (or core-shell particulate binders) of the present disclosure include: (a) methyl methacrylate (MMA), (b) methacrylic acid (MAA) or acrylic acid (AA), and (c) C 2 To C 6 Alkyl (meth) acrylate is used as an acryl-based monomer to achieve excellent bonding performance when used as an adhesive.
[0068] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may contain 10 wt % or more, 20 wt % or more, or 30 wt % or more of methyl methacrylate in the acryl-based monomer. The methyl methacrylate may be contained in the acryl-based monomer at 60 wt % or less, 50 wt % or less, or 40 wt % or less.
[0069] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may include 10 to 60 wt%, 20 to 50 wt%, 20 to 40 wt%, or 30 to 40 wt% of methyl methacrylate in the acryl-based monomer. Specifically, methyl methacrylate may be included in the acryl-based monomer at 20 to 40 wt%.
[0070] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may contain 10 wt % or more, 20 wt % or more, or 30 wt % or more of methacrylic acid or acrylic acid in the acryl-based monomer. The core-shell particles (or core-shell particulate binder) may contain 60 wt % or less, 50 wt % or less, or 40 wt % or less of methacrylic acid or acrylic acid in the acryl-based monomer.
[0071] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may include 10 to 60 wt%, 30 to 50 wt%, 20 to 50 wt%, 20 to 40 wt%, or 30 to 40 wt% of methacrylic acid or acrylic acid in the acryl-based monomer. Specifically, the core-shell particles (or core-shell particulate binder) may include 30 to 50 wt% of methacrylic acid or acrylic acid in the acryl-based monomer.
[0072] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may include 10 wt % or more, 20 wt % or more, or 30 wt % or more of C 2 To C 6 The core-shell particles (or core-shell particulate binder) may contain 60 wt % or less, 50 wt % or less, or 40 wt % or less of C 2-(2-methyl-2-yl)-4-nitropropene in the acryl-based monomer. 2 To C 6 Alkyl (meth)acrylate.
[0073] In an exemplary embodiment, the core-shell particles (or core-shell particulate binder) may include 10 wt % to 60 wt %, 30 wt % to 50 wt %, 20 wt % to 50 wt %, 20 wt % to 40 wt %, or 30 wt % to 40 wt % of C in the acryl-based monomer. 2 To C 6 Specifically, the acryl-based monomer may contain 20 wt % to 40 wt % of C 2 To C 6 Alkyl (meth)acrylate.
[0074] In addition, the present disclosure relates to a core-shell particle (or core-shell particle-like binder) slurry having a perfluorinated resin core comprising a perfluoropolymer and a resin shell layer comprising an acryl-based polymer, wherein the core-shell particle (or core-shell particle-like binder) is prepared by using a C-substituted alkyl group having one or more alkyl groups of the following chemical formula 1: 8 The invention relates to a method for preparing a fluorinated resin core by emulsion polymerization of an acryl-based monomer using a polyethylene glycol ether having a higher alkyl group as an emulsifier, wherein the acryl-based monomer comprises: (a) methyl methacrylate (MMA); (b) methacrylic acid (MAA) or acrylic acid (AA); and (c) C 2 To C 6 Alkyl (meth) acrylate:
[0075] [Chemical formula 1]
[0076] R-(-OC 2 H 4 -) n -OH
[0077] Wherein R is C substituted with one or more alkyl groups 8 or a higher alkyl group, and n is an integer of 5 to 15.
[0078] Additionally, the present disclosure may provide a composition comprising core-shell particles (or core-shell particulate binders).
[0079] In an exemplary embodiment, the composition may include an electrode active material. The composition including the core-shell particles of the present disclosure has excellent affinity with the active material and can show excellent binding properties even when the ratio of the perfluoropolymer (PTFE) included in the core-shell particles is small.
[0080] The present disclosure may provide a composition including a core-shell particle (or a core-shell particulate binder) and an electrode active material.
[0081] Furthermore, the present disclosure may provide an electrode manufactured from the composition.
[0082] The present disclosure can provide a battery comprising a core-shell particle (or a core-shell particulate binder) as a binder. When the particle is used as a binder during battery manufacturing, the core-shell particle (or core-shell particulate binder) of the present disclosure shows excellent binding properties with electrode active materials.
[0083] Hereinafter, the present invention will be described in more detail with reference to Examples and Comparative Examples. However, the following Examples and Comparative Examples are only examples for describing the present invention in more detail and do not limit the present invention in any way. Unless otherwise specified in the present invention, the unit of temperature is ° C, and unless otherwise specified, the unit of the amount of the composition used is weight %.
[0084] 1. Measurement of total solid content [g / mol]
[0085] 15 g of the latex after polymerization was weighed on an aluminum pan and dried in an oven at 80° C. for 24 hours, and then the weight after drying was measured. The total solid content was calculated by (weight after drying-pan weight) / initial weight×100.
[0086] 2. Extraction method of non-fluorinated resin
[0087] 100g of the latex after polymerization is placed in a 250ml centrifuge tube and centrifuged at 9,000rpm for 30 minutes. The separated supernatant is discarded, 100g of acetone is added to the remaining solid, and the oscillation is performed for 3 hours with an oscillator so that the non-fluorinated resin is extracted with acetone. After oscillation for 3 hours, centrifugation is performed again at 9,000rpm for 30 minutes, and the fluorinated resin is gathered at the bottom, and the acetone supernatant in which the non-fluorinated resin is dissolved is separated. The separated supernatant in which the non-fluorinated resin is dissolved is added dropwise to 400g of methanol to obtain the precipitated non-fluorinated resin. The precipitated non-fluorinated resin is separated using a decompression filter, washed 3 times with methanol, placed in a separate beaker, and dried in an oven at 80°C for 24 hours.
[0088] 3. Weight average molecular weight (Mw) [g / mol]
[0089] In order to measure the molecular weight of the non-fluorinated resin of the latex prepared in Examples and Comparative Examples, 10 mg of the extracted non-fluorinated resin was respectively dissolved in 10 ml of tetrahydrofuran (THF) and filtered using a 0.2 μm Teflon filter, and the molecular weight was measured using gel permeation chromatography (GPC) available from waters.
[0090] 4. Glass transition temperature (Tg) [℃]
[0091] The non-fluorinated resin extracted from the latex prepared in Examples and Comparative Examples was measured using differential scanning calorimetry (TA, Q20 DSC) under heating conditions of 10°C per minute within 2 cycles, and then the glass transition temperature was calculated using the inflection point of the second cycle by the semi-Cp method.
[0092] 5. Measurement of the ratio between fluorinated resin and non-fluorinated resin
[0093] 15 g of the latex after polymerization was placed on an aluminum pan and dried in an oven at 80° C. 10 mg of the dried powder was heated to 600° C. at 10° C. per minute by TGA, and the weight reduction was measured. The ratio between the fluorinated resin and the non-fluorinated resin was measured from the degree of weight reduction using the characteristics of the thermally decomposed non-fluorinated resin.
[0094] 6. Measurement of particle size
[0095] One or two drops of latex after polymerization were diluted 1,000 times, and the size and distribution of particles were measured using NICOMP 380 (Entegris, dynamic light scattering).
[0096] 7. Particle shape analysis and elemental analysis (FE-SEM / EDS)
[0097] 1 or 2 drops of latex after polymerization were diluted with 20 ml of water and dispersed in the 20 ml of water, and then 1 or 2 drops of the diluted solution were dropped onto a silicon wafer. The silicon wafer with the sample thereon was dried at room temperature for 2 to 3 hours under vacuum, and then coated with platinum for 90 seconds using sputtering. The shape of the particles was examined at a resolution of 30,000 to 100,000×1280 at an accelerating voltage of 5 kV and a current of 10 μA.
[0098] 8. Analysis of particle structure (TEM / EDS)
[0099] A drop of latex was dropped onto a grid for transmission electron microscopy (TEM) after plasma treatment and dried at room temperature. The structure of the dried sample was analyzed with a TEM / EDS (FEI, TECNAI TF20) accelerating voltage of 200 kV.
[0100] 9. Method for preparing electrode paste
[0101] A total of 100 g of 96 g NCM 622 (LG Chem), 2 g Ketjen black (EC-600JD available from Nouryon) and 2 g binder were added to a Henschel mixer and mixed for 4 minutes. After mixing, the composition was added to a HAAKE rheological mixer (model name) and shear force was applied to allow intimate bonding by fiberization to obtain a mixture as shown in FIG. Figure 1 The electrode paste shown.
[0102] 10. Bond strength screening method
[0103] The paste prepared according to the method for preparing an electrode paste was added to a sieving machine (Haver & Boecker) in which a cover, sieve 1 (hole size: 6.3 mm, wire diameter: 1.8 mm), sieve 2 (hole size: 4.75 mm, wire diameter: 1.6 mm) and a fan were laminated, and sieved for 1 minute under the condition of amplitude 1. The weight of the particles classified by sieving is shown in Table 2.
[0104] [Example 1]
[0105] A PTFE aqueous dispersion having an average particle size of 0.21 μm, a solid content concentration of 30%, and a standard specific gravity (SSG) of 2.16 to 2.22 was prepared. Subsequently, 2448.0 g of the PTFE dispersion and 48.96 g of a 90% aqueous solution of polyethylene glycol triphenyl nonyl ether (TMN100X available from Dow) (the molecular weight of the ethylene glycol repeating unit showing hydrophilicity is mainly 384 g / mol) were added to a 4-liter reactor and stirred at a speed of 350 rpm while heating to 75° C. under nitrogen bubbling.
[0106] After the temperature reached 75° C., which was the polymerization temperature, nitrogen bubbling was stopped, and 15 minutes later, a monomer mixed solution consisting of 36.72 g of methyl methacrylate (MMA), 91.8 g of methacrylic acid (MAA), 55.08 g of butyl acrylate (nBA) and 0.40 g of n-octyl mercaptan was added dropwise to the reactor over 15 minutes.
[0107] 15 minutes after the addition of the monomer mixed solution, 68.4 g of distilled water and 0.18 g of an aqueous solution of ammonium persulfate were added dropwise to the reactor over about 10 minutes. The polymerization reaction was carried out for 3 hours from the completion of the addition of ammonium persulfate, and then cooled to 30° C. to obtain an emulsion.
[0108] The weight ratios of the emulsions are shown in Table 1.
[0109] In addition, according to 9. Method for preparing electrode paste and 10. Bonding strength screening method, an electrode paste containing the emulsion as a binder was prepared, and the bonding strength was measured by the screening method. The results are shown in Table 2.
[0110] [Example 2]
[0111] The process was carried out in the same manner as in Example 1, except that the weight was changed to 73.44 g of methyl methacrylate (MMA), 55.08 g of methacrylic acid, 55.08 g of butyl acrylate (nBA), 0.29 g of n-octyl mercaptan, and 0.92 g of ammonium persulfate.
[0112] [Example 3]
[0113] The process was carried out in the same manner as in Example 1, except that the weight was changed to 1836.0 g of PTFE dispersion, 36.72 g of a 90% aqueous solution of polyethylene glycol triphenyl nonyl ether (TMN100X available from Dow) (the molecular weight of the ethylene glycol repeating unit showing hydrophilicity was mainly 384 g / mol), 428.4 g of additional water, 73.44 g of methyl methacrylate (MMA), 183.6 g of methacrylic acid, 110.16 g of butyl acrylate (nBA), 0.81 g of n-octyl mercaptan, and 0.37 g of ammonium persulfate.
[0114] [Example 4]
[0115] The process was carried out in the same manner as in Example 3 except that the weight was changed to 146.88 g of methyl methacrylate (MMA), 110.16 g of methacrylic acid, 110.16 g of butyl acrylate (nBA), 0.59 g of n-octyl mercaptan, and 1.84 g of ammonium persulfate.
[0116] [Example 5]
[0117] The process was carried out in the same manner as in Example 1, except that the weights were changed to 1224.0 g of PTFE dispersion, 24.48 g of a 90% aqueous solution of polyethylene glycol triphenyl nonyl ether (TMN100X available from Dow) (the molecular weight of the ethylene glycol repeating unit showing hydrophilicity was mainly 384 g / mol), 856.8 g of additional water, 110.16 g of methyl methacrylate (MMA), 275.40 g of methacrylic acid, 165.24 g of butyl acrylate (nBA), 1.21 g of n-octyl mercaptan, and 0.55 g of ammonium persulfate.
[0118] [Example 6]
[0119] The process was carried out in the same manner as in Example 5, except that the weight was changed to 220.32 g of methyl methacrylate (MMA), 165.24 g of methacrylic acid, 165.24 g of butyl acrylate (nBA), 0.88 g of n-octyl mercaptan, and 2.75 g of ammonium persulfate.
[0120] [Comparative Example 1]
[0121] The process was performed in the same manner as in Example 1, except that the weights were changed to 146.88 g of methyl methacrylate (MMA), 0 g of methacrylic acid, 36.72 g of butyl acrylate (nBA), 0.26 g of n-octyl mercaptan, and 0.92 g of ammonium persulfate.
[0122] [Comparative Example 2]
[0123] The process was performed in the same manner as in Comparative Example 1, except that the weight was changed to 137.7 g of methyl methacrylate (MMA) and 45.9 g of methyl acrylate (MA) instead of butyl acrylate (nBA).
[0124] [Comparative Example 3]
[0125] The process was performed in the same manner as in Example 3, except that the weights were changed to 293.76 g of methyl methacrylate (MMA), 0 g of methacrylic acid, 73.44 g of butyl acrylate (nBA), 0.51 g of n-octyl mercaptan, and 1.84 g of ammonium persulfate.
[0126] [Comparative Example 4]
[0127] The process was performed in the same manner as in Comparative Example 3, except that the weight was changed to 275.4 g of methyl methacrylate (MMA) and 91.80 g of methyl acrylate (MA) instead of butyl acrylate (nBA).
[0128] [Comparative Example 5]
[0129] The process was performed in the same manner as in Example 5, except that the weight was changed to 440.64 g of methyl methacrylate (MMA), 0 g of methacrylic acid, 110.16 g of butyl acrylate (nBA), 0.77 g of n-octyl mercaptan, and 2.75 g of ammonium persulfate.
[0130] [Comparative Example 6]
[0131] The process was performed in the same manner as in Comparative Example 5, except that the weight was changed to 413.1 g of methyl methacrylate (MMA) and 137.7 g of methyl acrylate (MA) instead of butyl acrylate (nBA).
[0132] [Table 1]
[0133]
[0134] [Table 2]
[0135]
[0136] As can be seen from the analysis results, when core-shell particles simultaneously containing methyl methacrylate (MMA), methacrylic acid (MAA) and butyl acrylate (nBA) as in Examples 1 and 2 of the present disclosure are used as a binder, the weight % of coarse particles measured in sieve 1 is as high as 90% or more, and it is confirmed that the particles are excellent in bonding strength with electrode active materials, etc. as a binder.
[0137] Furthermore, as shown in Examples 3 to 6, even when the amount of PTFE used was small, the weight % of the coarse particles was maintained at 90% or more, and it was confirmed that excellent bonding strength with an electrode active material and the like was maintained.
[0138] However, when methyl methacrylate and butyl acrylate were used in combination or methyl methacrylate and methyl acrylate were used in combination, as in Comparative Examples 1 to 6, the weight % of coarse particles was as low as 34%, and the weight % of fine particles was as high as 50% or more, and it was determined that the particles had weak bonding strength with electrode active materials, etc. as a binder.
[0139] In the above, the preferred exemplary embodiments of the present invention are described, however, various modifications and equivalent scopes can be used in the present invention, and it is obvious that the above embodiments can be appropriately modified and applied in the same manner. Therefore, the above description does not limit the scope of the present invention defined by the appended claims.
Claims
1. A core-shell particle comprising a perfluorinated resin core comprising a perfluorinated polymer and a resin shell layer comprising an acryl-based polymer, wherein the core-shell particles are manufactured by emulsion polymerizing an acryl-based monomer to the perfluorinated resin core using a polyethylene glycol ether having a C8 or higher alkyl group substituted with one or more alkyl groups of the following Chemical Formula 1 as an emulsifier, and The acryl-based monomer comprises: (a) Methyl methacrylate; (b) methacrylic acid or acrylic acid; and (c) C2 to C6 alkyl (meth)acrylate: [Chemical formula 1] R-(-O-C2H4-) n -OH wherein R is a C8 or higher alkyl group substituted with one or more alkyl groups, and n is an integer from 5 to 15.
2. The core-shell particle according to claim 1, wherein Chemical Formula 1 is an emulsifier of the following Chemical Formula 2: [Chemical formula 2] 3. The core-shell particle of claim 1, wherein the perfluoropolymer is polytetrafluoroethylene. 4 . The core-shell particle of claim 1 , wherein the core-shell particle comprises the perfluoropolymer and the acryl-based polymer in a weight ratio of 98:2 to 30:
70. 5 . The core-shell particle according to claim 4 , wherein the core-shell particle comprises the perfluoropolymer and the acryl-based polymer in a weight ratio of 80:20 to 40:
60. The core-shell particle according to claim 1 , wherein the methyl methacrylate is contained in the acryl-based monomer at 20 to 40 wt %. 7 . The core-shell particle according to claim 1 , wherein the methacrylic acid or the acrylic acid is contained in the acryl-based monomer at 30 to 50 wt %. 8 . The core-shell particle according to claim 1 , wherein the C2 to C6 alkyl (meth)acrylate is contained in the acryl-based monomer at 20 to 40 wt %.
9. A composition comprising the core-shell particle according to claim 1 and an electrode active material.
10. An electrode made from the composition according to claim 9.
11. A battery comprising the core-shell particle according to claim 1 as a binder.
Citation Information
Patent Citations
Core-shell type particle, dispersion and powder
IN202037027466A
Fluorine-acryl resin composite emulsion and process of preparing the same by forming shell of alkylester acrylate and alkylester methacrylate polymer on fluorine resin gel core
KR1019990065951A
PTFE-based polymers
US20020193495A1
Core-shell type particle, dispersion and powder
US20210070974A1